2010
DOI: 10.1128/aem.00704-10
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol Reduces the Expression of Virulence-Related Exoproteins in Staphylococcus aureus

Abstract: Eugenol, an essential oil component in plants, has been demonstrated to possess activity against both Gram-positive and Gram-negative bacteria. This study examined the influence that subinhibitory concentrations of eugenol may have on the expression of the major exotoxins produced by Staphylococcus aureus. The results from a tumor necrosis factor (TNF) release assay and a hemolysin assay indicated that S. aureus cultured with graded subinhibitory concentrations of eugenol (16 to 128 g/ml) dose dependently decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 37 publications
2
83
0
1
Order By: Relevance
“…Eugenol also exhibited synergic interactions with cinnamate, cinnamaldehyde, thymol and carvacrol, resulting greater antibacterial activity [33][34]. Sub-inhibitory concentrations of eugenol (16-128 µg/ mL) dose-dependently decreased the necrosis factor-inducing and haemolytic activities of culture supernatants and significantly reduced the production of staphylococcal enterotoxin A [35]. The drawbacks of eugenol i.e, low solubility, liability to sublimation and strong odor, could be overcome by glycosylation to eugenol α-D-glucopyranoside (α-EG), which is more effective than that of pure eugenol as tested with Staphylococcus aureus and E. coli [36].…”
Section: Antioxidant Activity Of Eugenolmentioning
confidence: 99%
“…Eugenol also exhibited synergic interactions with cinnamate, cinnamaldehyde, thymol and carvacrol, resulting greater antibacterial activity [33][34]. Sub-inhibitory concentrations of eugenol (16-128 µg/ mL) dose-dependently decreased the necrosis factor-inducing and haemolytic activities of culture supernatants and significantly reduced the production of staphylococcal enterotoxin A [35]. The drawbacks of eugenol i.e, low solubility, liability to sublimation and strong odor, could be overcome by glycosylation to eugenol α-D-glucopyranoside (α-EG), which is more effective than that of pure eugenol as tested with Staphylococcus aureus and E. coli [36].…”
Section: Antioxidant Activity Of Eugenolmentioning
confidence: 99%
“…Esse óleo contém os compostos majoritários eugenol 85,3%; β-cariofi leno 11,8% e α-humuleno, 1,5%; segundo cromatograma disponibilizado no sítio da empresa FERQUIMA para o lote utilizado nessa pesquisa. Apesar de não ser o único componente que desempenhe ação antibacteriana, o eugenol tem sua atividade antimicrobiana comprovada (LEUSCHNER & ZAMPARINI, 2002;QIU et al, 2010). MOREIRA et al (2005), estudando vários óleos essenciais contra E. coli O 157:H7, observaram maior efetividade do óleo de cravo da índia, MIC de 0,25%, igual ao valor encontrado para o presente trabalho.…”
Section: Resultado E Discussãounclassified
“…Because of their potent antimicrobial properties against a broad spectrum of microorganisms such as S. aureus, Salmonella, and Listeria monocytogenes, plant extracts, especially phytochemicals they contain, have gained great interest (Cowan, 1999;Carson et al, 2006). Many studies have been reported that natural extracts such as oil, licochalcone A, and eugenol have an antimicrobial function (Burt, 2004;Qiu et al, 2010aQiu et al, , 2010b.…”
Section: Introductionmentioning
confidence: 99%